Generational shifts in atopic disease among immigrant families to North America from Southern India - Sangeetha M. Kodoth, MD; Priyanka Dadha, PhD; Shruti Sehgal, MD(Hom), MS; Christopher Warren, PhD; Sai R. Nimmagadda, MD; Lucy A. Bilaver, PhD; Ruchi S. Gupta, MD, MPH (Journal of Allergy and Clinical Immunology: Global, 2025)
Background: The Indian diaspora is a fast-growing population in North America, but there are limited data on the prevalence of atopic diseases after migration. Objective: We investigated the impact of migration on atopic disease prevalence among physician families who migrated from Kerala, Southern India, to North America. Methods: A cross-sectional questionnaire was administered to collect demographic information, migration, and atopic history—including allergic rhinitis (AR), food allergy (FA), asthma, and atopic dermatitis (AD)—of physician migrants from Kerala, Southern India, and their families. Results: Of the 164 completed surveys, 148 were included in the final analyses. Postmigration prevalence of AR and FA were significantly higher than premigration prevalence (AR-pre 12.8% [95% confidence interval (CI), 8.1-19.6] vs AR-post 21.6% [95% CI, 15.5-29.3] [P = .048], and FA-pre 2.7% [95% CI, 0.9-7.2] vs FA-post 9.5% [95% CI, 5.5-15.7] [P = .022]). Cow’s milk (4.1%) was the common food trigger reported, followed by fruits (2.0%) and shellfish (2.0%). In 137 respondent families with children, North America–born compared to migrant children had a higher prevalence of asthma (18.6% [95% CI, 13.4-25.1] vs 8.6% [95% CI, 4.1-16.7] [P = .033]), AR (36.1% [95% CI, 29.2-43.5] vs 19.4% [95% CI, 12.2-29.1] [P = .005]), and FA (17.5% [95% CI, 12.4-23.9] vs 5.4% [95% CI 2.0-12.7] [P = .008]). Conclusion: Respondents exhibited increased prevalence of AR and FA after migration. North America–born children showed elevated risk for asthma, AR, and FA compared to respondents and children who migrated after birth. Research into lost protective factors and new risk factors, including environmental and dietary changes, is needed to decrease the impact on future generations.